Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1002/ajmg.1320390409
|View full text |Cite
|
Sign up to set email alerts
|

Ullrich‐Turner syndrome in mother and daughter: Prenatal diagnosis of a 46, X, del(X)(p21) offspring from a 45, X mother with low‐level mosaicism for the del(X)(p21) in one ovary

Abstract: A woman with Ullrich-Turner syndrome but with normal secondary sex characteristics became pregnant on two occasions (ages 23 and 24). She had a 45,X karyotype in 100/100 lymphocytes and 50/50 skin fibroblasts. The first pregnancy ended in a miscarriage at 2 months of gestation. In the second pregnancy cultured amniocytes showed a 46,X,del(X)(p21) karyotype. This pregnancy resulted in an apparently normal girl. Biopsies of the mother's ovaries were obtained at the time of cesarean section. Grossly the ovaries a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 13 publications
0
12
0
1
Order By: Relevance
“…The existence tissue‐specific differences may help to interpret the phenotypic variation of Turner syndrome. Several studies have shown such tissue‐specific mosaicism in patients with 45,X cell line [16–18].…”
Section: Discussionmentioning
confidence: 99%
“…The existence tissue‐specific differences may help to interpret the phenotypic variation of Turner syndrome. Several studies have shown such tissue‐specific mosaicism in patients with 45,X cell line [16–18].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the hereditary nature of the ring chromosome and other mosaic forms have been reported (9,10). Couples diagnosed with TS should be informed of the high probability of gonadal failure and infertility in their future children and the high risk of miscarriage and of fetal and/or chromosomal abnormalities in the offspring.…”
Section: Figurementioning
confidence: 98%
“…Familial occurrence of Ullrich-Turner syndrome has been described in only few reports [Ayuso et al, 1984;Blumenthal et al, 1997;Fitzgerald et al, 1984;Fryns et al, 1982;Fryns et al, 1988;Varela et al, 1991;Verschraegen-Spae et al, 1992;Zinn et al, 1997]. In this case the mother, with extreme mosaicism in the lymphocytes and also short stature as a typical finding in the Ullrich-Turner syndrome is still fertile, suggesting a preponderance of cells with the karyotype 46,X,del(Xp21) in the gonads.…”
Section: American Journal Of Medical Genetics 80:436-438 (1998)mentioning
confidence: 61%